Efficacy and safety of bempedoic acid for the treatment of hypercholesterolemia: A systematic review and meta-analysis. - Arrigo F G Cicero; Federica Fogacci; Adrian V Hernandez; Maciej Banach; Lipid and Blood Pressure Meta-Analysis Collaboration (LBPMC) Group and the International Lipid Expert Panel (ILEP) (PLoS Medicine, 2020)
Background Bempedoic acid is a first-in-class lipid-lowering drug recommended by guidelines for the treatment of hypercholesterolemia. Our objective was to estimate its average effect on plasma lipids in humans and its safety profile. Methods and findings We carried out a systematic review and meta-analysis of phase II and III randomized controlled trials on bempedoic acid (PROSPERO: CRD42019129687). PubMed (Medline), Scopus, Google Scholar, and Web of Science databases were searched, with no language restriction, from inception to 5 August 2019. We included 10 RCTs (n = 3,788) comprising 26 arms (active arm [n = 2,460]; control arm [n = 1,328]). Effect sizes for changes in lipids and high-sensitivity C-reactive protein (hsCRP) serum concentration were expressed as mean differences (MDs) and 95% confidence intervals (CIs). For safety analyses, odds ratios (ORs) and 95% CIs were calculated using the Mantel-Haenszel method. Bempedoic acid significantly reduced total cholesterol (MD -14.94%; 95% CI -17.31%, -12.57%; p < 0.001), non-high-density lipoprotein cholesterol (MD -18.17%; 95% CI -21.14%, -15.19%; p < 0.001), low-density lipoprotein cholesterol (MD -22.94%; 95% CI -26.63%, -19.25%; p < 0.001), low-density lipoprotein particle number (MD -20.67%; 95% CI -23.84%, -17.48%; p < 0.001), apolipoprotein B (MD -15.18%; 95% CI -17.41%, -12.95%; p < 0.001), high-density lipoprotein cholesterol (MD -5.83%; 95% CI -6.14%, -5.52%; p < 0.001), high-density lipoprotein particle number (MD -3.21%; 95% CI -6.40%, -0.02%; p = 0.049), and hsCRP (MD -27.03%; 95% CI -31.42%, -22.64%; p < 0.001). Bempedoic acid did not significantly modify triglyceride level (MD -1.51%; 95% CI -3.75%, 0.74%; p = 0.189), very-low-density lipoprotein particle number (MD 3.79%; 95% CI -9.81%, 17.39%; p = 0.585), and apolipoprotein A-1 (MD -1.83%; 95% CI -5.23%, 1.56%; p = 0.290). Treatment with bempedoic acid was positively associated with an increased risk of discontinuation of treatment (OR 1.37; 95% CI 1.06, 1.76; p = 0.015), elevated serum uric acid (OR 3.55; 95% CI 1.03, 12.27; p = 0.045), elevated liver enzymes (OR 4.28; 95% CI 1.34, 13.71; p = 0.014), and elevated creatine kinase (OR 3.79; 95% CI 1.06, 13.51; p = 0.04), though it was strongly associated with a decreased risk of new onset or worsening diabetes (OR 0.59; 95% CI 0.39, 0.90; p = 0.01). The main limitation of this meta-analysis is related to the relatively small number of individuals involved in the studies, which were often short or middle term in length. Conclusions Our results show that bempedoic acid has favorable effects on lipid profile and hsCRP levels and an acceptable safety profile. Further well-designed studies are needed to explore its longer-term safety.